Conjuntos de bases para todos elétrons de H até Xe específicos para cálculos ZORA: aplicações em átomos e moléculas - Gomes, Carolayne Silva (2024)
Segmented basis set of quadruple zeta valence quality plus polarization functions (QZP) for H through Xe was developed to be used in conjunction with the ZORA Hamiltonian. This set was augmented with diffuse functions to adequately describe electrons farther away from the nuclei. Using the ZORA-CCSD(T)/QZP-ZORA theoretical model, atomic ionization energies and bond lengths, harmonic vibrational frequencies, and atomization energies of some molecules were calculated. It is verified that the addition of core-valence corrections improves the agreement between the theoretical and experimental results of the molecular properties. For atomization energies, a similar finding occurs when spin-orbit couplings are considered. With the augmented QZP-ZORA set, static mean dipole polarizabilities of a set of atoms were computed and compared with previously published recommended and experimental values. For each property studied, evaluations of the ZORA and Douglas-Kroll-Hess Hamiltonians were made.